GAGASAN PEMBENTUKAN PENGADILAN KHUSUS PERTANAHAN DI INDONESIA - Maharani Nurdin (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
Land disputes occur because the land has an important position. The land has a function in the framework of the integrity of the state and function as a basic capital to realize the greatest prosperity of the people. The government has provided a means to resolve land disputes, through litigation and non-litigation. The establishment of the Special Land Court is the only alternative in these conditions. The establishment of this special court for Land Affairs can be carried out using Law Number 48 of 2009 concerning Judicial Power as its legal basis, which is also stated in the Draft Law on the Agrarian Court. The research method in this study is normative juridical. The data collection method uses library research. The results showed that to fulfill the fundamental principles of human life as mandated by Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, namely legal protection for the community in land rights, agrarian conflict is no longer considered an ordinary problem but has become a problem of a nature extraordinary, therefore it is necessary to have a Special Agrarian Court. The inability of Litigation and non-litigation bodies to settle land disputes, the judges lack special specialization concerning agrarian matters. The Legal Position of the Special Land Court in the justice system in Indonesia is within the general court environment under the Supreme Court of the Republic of Indonesia. The Special Land Court can have a special function only to conduct examinations and hearings on land disputes and with special procedural law will be able to resolve land dispute problems.